Columnar Liquid Crystalline Self‐Assembly of Hydrogen‐Bonded Rod–Coil Diblock Complexes Created from Pyrazole/Benzoic acid Derivatives. (4th October 2015) - Kim, Ho‐Joong; Cho, Sung; Park, Jung Su
Abstract : The hydrogen‐bonded rod–coil diblock complexes consisting of bithiophene‐conjugated pyrazole derivatives and alkoxy‐substituted benzoic acid derivatives display supramolecular liquid crystal properties. Abstract : We synthesized hydrogen‐bonded rod–coil diblock complexes having both a rigid rod and a flexible coil by combining bithiophene‐conjugated pyrazole derivatives and alkoxy‐substituted benzoic acid derivatives. Their self‐assembled nanostructures were investigated using polarized optical microscopy, molecular modeling, and X‐ray scattering in liquid crystalline (LC) state. They form different types of supramolecular LC phases depending on the numbers and lengths of alkoxy substituents in the benzoic acids. Diblock complexes with low volume ratios of aliphatic coils to rod segments (dioctyloxy chains) self‐assembled into lamellar phases; systems with higher ratios (didodecyloxy, trioctyloxy, and tridodecyloxy chains) formed columns. In these columnar structures, two pyrazoles and two benzoic acids formed an aromatic tetramer core through N–H···O and O–H···N hydrogen bonds. Two sets of aromatic tetramers surrounded by flexible aliphatic chains were then stacked to give columnar phases. These are novel examples of supramolecular LC structures comprising hydrogen‐bonded pyrazole–benzoic acid derivatives with tetrameric rigid aromatic scaffolds.